Editor's Welcome - Karen McGarry (Dalhousie University Libraries, 2021)
This past summer, I took over the role of Editor-in-Chief of JUE from Dr. Martha Radice. For many reasons, I am honoured to be taking over the editorial responsibilities for JUE. In an increasingly neoliberal environment where there is significant pressure for both academics and students to expedite research publications, undergraduate students often face fewer research opportunities and increasing competition to acquire suitable, high-quality outlets for publication. For the past 11 years, JUE has provided undergraduate student authors the opportunity to obtain critical, peer reviewed feedback from top scholars who serve as JUE Editorial Board members, to engage in the recursive writing process, and to publish their original, ethnographic research. This ultimately helps mentor talented students through the process of peer review and publication, and it instils in students a sense of pride and confidence in their work.